STANDAR PROFESI HUKUM DAN KONTRIBUSI PENDIDIKAN TINGGI DALAM MEWUJUDKAN PROFESI HUKUM YANG PROFESIONAL DI ERA DISRUPTIF - Ahmad Syaifudin (Fakultas Hukum Universitas Islam Malang, 2021)
The shift in working patterns that are so fast at Disruptive Era in the legal profession gives strong demands to legal professionals to quickly adapt, the right adaptations of course that will make a positive contribution to the realization of a legal climate that leads to just law. Everything returns to the Professional Actors, the more qualified professional actors and the understanding of the importance of being professional will greatly impact the achievement of the principle of legal objectives. In this study, the authors used a normative juridical method using a statutory approach and a historical approach. From the research it can be concluded that the quality of the education process carried out with the right standards / criteria will greatly affect the quality of legal profession actors, understanding of knowledge, the ability to implement knowledge and work attitudes in accordance with the norms determined and contained in the professional code of ethics. will create a positive climate for the realization of a just law in our country.